Sociodemographic factors are related to hair sample collection in economically marginalized families - Jiying Ling; Dalton Goodwin; Charles Given (Future Science OA)
Aim: Limited research has explored factors influencing participants' decisions to consent to and complete hair sample collection. This study examined the relationships of sociodemographics, perceived stress and coping with hair sample collection among children aged 3–5 years and parents.Research design & methods: Data were analyzed from 188 parent-child dyads. Among these, 78% of parents provided consent to hair sample collection. Hair samples were collected from 81% children and 68% parents.Results: Parents who provided consent reported higher levels of stress and used more avoidant coping strategies compared with those who did not. Parents who provided a hair sample engaged in less problem-focused coping. Children who were girls, non-Hispanic and White had higher odds of completing hair sample collection. Additionally, children were more likely to complete hair sample collection if their parents were married, employed full-time, or had an annual family income of ≥$20,000. Pregnant women and full-time employed parents also had higher odds of completing hair sample collection.Conclusion: The study identified important sociodemographic factors that may influence hair sample collection in research. To improve participation, tailored approaches such as at-home self-collection, sensitive hair cutting approaches to maintain participants' hair style, and addressing participants' unique barriers are recommended.